Hyaluronic acid and human/bovine serum albumin shelled nanocapsules: Interaction with mucins and in vitro digestibility of interfacial films. - del Castillo-Santaella, Teresa; Aguilera Garrido, Aixa; Galisteo González, Francisco; Gálvez Ruiz, María José; Molina-Bolívar, José Antonio; Maldonado-Valderrama, Julia (Elsevier, 2022)
Liquid lipid nanocapsules are oil droplets surrounded by a protective shell, which enable high load and allow controlled delivery of lipophilic compounds. However, their use in food formulations requires analysing their digestibility and interaction with mucin. Here, serum albumins and hyaluronic acid shelled olive oil nanocapsules are analysed to discern differences between human and bovine variants, the latter usually used as model system. Interfacial interaction of albumins and hyaluronic acid reveals that human albumin presents limited conformational changes upon adsorption, which increase by complexation with the polysaccharide present at the interface. The latter also promotes hydrophobic interactions with mucin, especially at pH 3 and protects albumin interfacial layer under in vitro gastric digestion. The interfacial unfolding induced in human albumin by hyaluronic acid facilitates in vitro lipolysis while its limited conformational changes provide the largest protection against in vitro lipolysis.
Keywords: Acido hialurónico; Mucopolisacáridos; Hyaluronic acid; Mucins